Increasing Student Motivation and Capability at Al-Hasan Al-Qur'an Education Park, Jipang Village, Cepu District, Blora Regency: Peningkatan Motivasi dan Kapabilitas Santri Taman Pendidikan Al-Qur'an Al-Hasan Desa Jipang Kecamatan Cepu Kabupaten Blora - Nurhayati, Siti Fatimah (Prosiding University Research Colloquium, 2024)
Improving education and health plays an important role in improving the quality of human resources (HR) which are very necessary for development. The community service carried out at the Al-Hasan Al-Qur'an educational park (TPA) in Jipang village, Cepu sub-district, Blora district aims to motivate Al-Hasan TPA students to improve their competence, especially in the field of emotional spiritual quation (ESQ), which is very necessary in this era. globalization as it is now considering that children are the nation's next generation. Community service activities are realized in the form of various religious competitions to commemorate Islamic religious holidays. The service was welcomed by parties related to TPA Al-Hasan. This activity is expected to strengthen their Islamic faith and beliefs as the basis for forming their personality and Islamic education. With this effort, it is hoped that it can help improve the quality of human resources so that they have high competitiveness and productivity which is very necessary for the development and progress of the Indonesian nation.